MODEL POLA ASUH ORANGTUA TERHADAP PERILAKU ANAK - Sari, Ilda Permata; Elvawati, Elvawati; Yatim, Yenita (Universitas Tanjungpura, 2022)
This research is motivated by working parents, both parents work in the informal sector. Working parents are busy outside the home which can lead to a lack of communication between parents and children so that parents do not know about their child